1992
DOI: 10.1111/j.1365-2184.1992.tb01452.x
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle analysis of asexual stages of erythrocytic malaria parasites

Abstract: Intra-erythrocytic Plasmodium species can be stained with the DNA binding dye, Hoechst 33342, and the distribution of DNA content determined for parasite populations by flow cytometric measurement of fluorescence. Analysis of this distribution will determine the parasitaemia (percentage of erythrocytes infected), and the percentages of trophozoite infected red blood cells, polyparasitized (trophozoite) red blood cells, and schizont/segmenter infected red blood cells. This analysis is based on the hypothesis th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
25
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…These characteristics make its utilization in malaria drug discovery an important advantage in terms of cost effectiveness and it has already been successfully used for testing human samples (32). However, its application has remained problematic in murine models of malaria due to the presence of a relatively high percentage of erythrocytes that contain significant amounts of nucleic acids (2,6,33). An interesting alternative could be the use of green fluorescent protein-transformed plasmodia, as recently described for P. berghei (34).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These characteristics make its utilization in malaria drug discovery an important advantage in terms of cost effectiveness and it has already been successfully used for testing human samples (32). However, its application has remained problematic in murine models of malaria due to the presence of a relatively high percentage of erythrocytes that contain significant amounts of nucleic acids (2,6,33). An interesting alternative could be the use of green fluorescent protein-transformed plasmodia, as recently described for P. berghei (34).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, as suggested by Jacobberger et al (6), Howell-Jolly bodies might establish a limit to sensitivity and specificity. This technical difficulty for measurement of parasitemias in murine models of malaria decreases sensitivity to 0.1% to 0.2% under the best conditions (2).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, several aspects remain poorly understood, particularly in connection with the G2 and M phases [8,9]. In the present study we demonstrate the stage-specific antimalarial activity of simaomicin a , although the mechanism of action remains unresolved.…”
mentioning
confidence: 59%
“…is as follows. G0-like phase is a merozoite (both free and late segmenters) form; G1 phase is an early trophozoite stage; S phase is soon after the appearance of pigmented trophozoites (this phase is considered as the trophozoite stage in this experiment); M phase is after the first nuclear division (this is considered as the schizont stage in this experiment); and the G2 phase, which is still unclear [8,9]. Naughton and Bell reported that drugs such as Hoechst 33342, roscovitine and L-mimosine blocked the trophozoite-schizont boundary, presumably in the S or G2 phase.…”
mentioning
confidence: 96%